Effect of Avocado Seed Ethanol Extract (Persea americana Mill) on Superoxide Dismutase (SOD1) and Histological Expression of Pancreas in Rats (Rattus norvegicus) with Diabetes Millitus - Fauziah Usman; Nurhaida Nurhaida; Binawati Ginting; Aulanni’am Aulanni’am (The Journal of Pure and Applied Chemistry Research, 2023)
Diabetes mellitus causes a pancreatic β-cells damage due to the increase of oxidative stress, thereby reducing Superoxide Dismutase 1 (SOD1) activity. This enzyme activity can be increased by utilizing antioxidant compounds from the avocado seed extract. This study aims to determine the increase of SOD1 expression and the repair of pancreatic β-cells tretaed with the ethanol extract of avocado seeds (Persea americana Mill). It is also aimed to observe the expression of pancreatic SOD1 and its histopathology change. The expression was measured by using immunohistochemical. This research used 20 Wistar rats aged of 2-3 moths, weighing of 150-200 grams. The diabetic rats were induced by streptozotocin (STZ) with dose of 30 mg/kg BW intraperitoneally. The rats were divided into 5 groups, namely: group 1 is healthy rats, group 2 is diabetic rats, while the group 3, 4 and 5 are therapeutic groups with 300, 350 and 400 mg/kg BW doses of ethanol extract for 14 days treatment. The results showed the ethanolic extract of avocado seeds has a potential as an antidiabetic agents based on the increase of pancreatic SOD1 (p<0.05) significantly, increase of SOD1 expression 7.6 ± 1.34, 11.6 ± 1.94 and 13.0 ± 2.82 in three different doses therapy (300, 350 and 400 mg/kg BW), and repairing structure of β-pancreatic cells on the therapeutic groups.